Mathematical Connection in Terms of Student Learning Styles of the Tenth Grade on the REACT Model Learning - Asiyah, Siti Nur; Suyitno, Amin; Safa'atullah, Muhammad Fajar (Department of Mathematics, Universitas Negeri Semarang, 2017)
The purposes of this research were (1) the learning outcomes on the aspects of mathematical connection ability of students on learning REACT model reached learning criterion, (2) the learning outcomes on aspects of mathematical connection ability among students on learning REACT model better than the students on learning Expository model, (3) there were differences in learning outcomes in aspects of mathematical connection ability between students who have learning styles of VAK and (4) there was interaction between learning model and student learning style to learning outcomes on aspects of students. This research type was quantitative with population of student of class X and selected two classes as sample. Data collection techniques were observation, interview, tests, questionnaires, and documentation. The results were (1) the ability of students mathematical connections on learning REACT model can fulfill the learning mastery individually and classically; (2) the average of students on mathematical connection aspect in learning of REACT model was better than the average of students on mathematical connection aspect in learning of Expository model; (3) there was a differences in the students ability on the mathematical connection aspects based on the learning style of VAK; (4) there was an interaction between the REACT learning model and the learning style of the students on the mathematical aspects of connection.